Assessing Micro, Small and Medium Enterprises as an Instrument for Human Capital Development and Poverty Reduction in Abuja Area Councils of Nigeria - Marcus Garvey ORJI; Kizito OLANIYI; Timothy ADEYEMO (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
The objective of this study was to assess the role of Micro, Small and Medium Enterprise as an instrument of human capital development and poverty reduction in the Bwari Area Council of Nigeria. The study was a survey research sampling the opinion of 184entrrepreneurs in the Area Council. Their opinion was collected using a structured questionnaire. The data obtained was analysed by tabulation and percentages, and the formulated hypotheses tested using Kendal coefficient of concordance method. The findings revealed that MSMEs contributes to human capital developments and is a strategy for eradication of poverty, because it creates jobs for people, and improves their standard of living; and MSMEs contributes to increase in income level of people in the area. The study concluded that MSMEs functions as a nursery for developing entrepreneur talent, and therefore recommended among others that, Government procurement policy that supports locally produced goods and services especially of small and medium size enterprises must be implemented, to help improve the activities of MSME in Bwari Area Council, so as to reduce poverty among the populace. Also more infrastructures should be provided by Bwari Area Council Administration. When basic infrastructures are provided, the entrepreneurs and MSMEs will be motivated to take advantage of such amenities, expand their operations, employ more hands, and reduce unemployment and poverty.